"Mad Men" and television aesthetics: Final shots as a tool for textual configuration - Huerta, Miguel A.; Pérez, Ernesto (Arte, Individuo y Sociedad, 2019)
Academic studies of Mad Men confirm that television aesthetics awaken a secondary interest among scholars. The present work joins the body of critical literature that defends the importance of style to television programming. In spite of the thrust and value of the new results achieved by television aesthetics, it is enough to look into the existing bibliography about works like Mad Men to arrive at the conclusion that their scope continues to be comparatively residual. In concrete terms, a formal analysis (scale, placing, length, angle, movement, composition, etc.) of the ‘shot unit’ related to this series is proposed. This will examine the 92 units that comprise the final shot of each episode of Mad Men, to yield the quantitative and qualitative elements that help forge the ‘aesthetic of emptiness’ that characterizes the TV show created by Matthew Weiner. The final images of each installment make up a kind of unhurried ritual in which the television form portrays a man on his own, trapped in an oppressive setting and unable to progress dramatically.